CuO@NiO core-shell nanoparticles decorated anatase TiO2 nanospheres for enhanced photocatalytic hydrogen production. (6th March 2020) - Ravi, P.; Navakoteswara Rao, V.; Shankar, M.V.; Sathish, M.
Abstract: Core-shell structured co-catalyst has been created much attention in photocatalytic hydrogen production due to their efficient electron-hole pair separation, suppression of surface back reaction and long term stability. Here, we report the preparation of CuO@NiO hierarchical nanostructures as a co-catalyst deposited on TiO2 nanospheres for enhanced photocatalytic hydrogen generation. The formation of ultrathin NiO shell over the CuO core was confirmed by TEM analysis. Fabricated core-shell nanostructured CuO@NiO over TiO2 nanospheres was studied for hydrogen evolution under the direct solar light and it showed a high rate of H2 production of 26.1 mmol. h −1 . g −1 cat . It was scrutinized that the rate of hydrogen production was improved with shell thickness and co-catalyst loading. Systematic investigation on CuO@NiO co-catalyst loading, pH of the medium and glycerol concentration for augmented H2 production. The recorded rate of hydrogen production is almost six folds greater than that of pristine TiO2 . In the view of largescale synthesis for alternative energy storage applications, the composited photocatalyst was made of by simple mixing method, which could be scaled up without any loss in photocatalytic activity. Further, the stability test of photocatalyst for continuous use found that 82% of initial photocatalytic activity is retained even after three days. Graphical abstract: Image 1 Highlights: CuO@NiO core-shell structured co-catalysts on TiO2 was prepared. The photocatalytic performance was examined using aqueous glycerol solution. Co-catalyst loading and NiO shell thickness significantly influenced H2 evolution. Effect of pH and Glycerol concentration on hydrogen evolution was studied.